2018
DOI: 10.4103/aam.aam_30_17
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally extensive transverse myelitis following dengue virus infection: A rare entity

Abstract: Association of dengue fever with longitudinally extensive transverse myelitis in pediatric age group is a rare entity. We describe a case of 15 year old adolescent male who presented with dengue fever and in whom symptoms of transverse myelitis developed 4 weeks after fever (post-infectious stage). Magnetic resonance imaging confirmed the diagnosis of longitudinally extensive transverse myelitis involving dorso-lumbar cord. Patient recovered almost completely with minimal residual neurological deficit after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Li HM et al conducted a cohort study that identified an association between dengue infection and the development of autoimmune diseases, including SLE, Reiter's syndrome, multiple sclerosis, myasthenia gravis, autoimmune encephalomyelitis, systemic vasculitis, and primary adrenocortical insufficiency (10). Several case reports revealed that the infection occurred following autoimmune diseases, such as SLE, lupus nephritis, necrotizing scleritis, multifocal motor neuropathy, neuromyelitis optica spectrum disorder, longitudinally extensive transverse myelitis, anti-glomerular basement membrane disease (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Dengue myopathy was also reported (25).…”
Section: Discussionmentioning
confidence: 99%
“…Li HM et al conducted a cohort study that identified an association between dengue infection and the development of autoimmune diseases, including SLE, Reiter's syndrome, multiple sclerosis, myasthenia gravis, autoimmune encephalomyelitis, systemic vasculitis, and primary adrenocortical insufficiency (10). Several case reports revealed that the infection occurred following autoimmune diseases, such as SLE, lupus nephritis, necrotizing scleritis, multifocal motor neuropathy, neuromyelitis optica spectrum disorder, longitudinally extensive transverse myelitis, anti-glomerular basement membrane disease (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Dengue myopathy was also reported (25).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of high protein and leukocyte levels in the CSF could indicate an acute inflammatory process due to the viral local effect, as well 61 . Some diagnostic imaging methods such as MRI can also be performed to detect signs of inflammation and for differential diagnosis 57 .…”
Section: Myelitismentioning
confidence: 99%
“…There is no high-level evidence to support the use of intravenous corticosteroids, however, pulse therapy with methylprednisolone is still the main option. Therapeutic plasma exchange can also be used as a second choice 57 . A case report of a 24-year-old woman, who tested positive for dengue IgM/IgG antibodies and presented acute myelitis, showed that even being treated with IV pulse methylprednisolone immunoglobulin plasmapheresis and physiotherapy, it was not possible to obtain a complete recovery in her motor and sensory deficits after 5 months 63 .…”
Section: Myelitismentioning
confidence: 99%
“…Li HM et al conducted a cohort study that identified an association between dengue infection and the development of autoimmune diseases, including SLE, Reiter's syndrome, multiple sclerosis, myasthenia gravis, autoimmune encephalomyelitis, systemic vasculitis, and primary adrenocortical insufficiency (10). Several case reports revealed that the infection occurred following autoimmune diseases, such as SLE, lupus nephritis, necrotizing scleritis, multifocal motor neuropathy, neuromyelitis optica spectrum disorder, longitudinally extensive transverse myelitis, anti-glomerular basement membrane disease (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Dengue myopathy was also reported (25).…”
Section: Discussionmentioning
confidence: 99%